The Concept of ‘Radio Music’: Special section: RadioMusic. Papers from the LARM conference ‘Digital Archives, Audiovisual Media and Cultural Memory’ Copenhagen, 14–15 November 2013 - Fjeldsøe, Michael (Danish Yearbook of Musicology, 2016)
In the late 1920s, young composers and musicians turned towards new fi elds of activity and new media in order to reach a larger audience. In Germany, this effort was part of the movement of Neue Sachlichkeit, and for a short period of time Radiomusik was considered the ideal means for a democratic, educational and didactic effort which would enlighten all of society. For a while it seemed that radio music was considered a genre of its own. To fulfi l its function, radio music had to consider technical limitations as well as the educational level and listening modes of the new mass audience. Public radio, as discussed by Kurt Weill and Paul Hindemith, was at fi rst greeted with great expectations, but soon a more realistic attitude prevailed. Weill, himself a radio critic as well, composed Der Lindberghflug (1929) as a piece of ‘radio music theatre’, but then changed some of its features in order to turn it into a didactical play for amateurs, a so-called Lehrstück. The article presents the concept of ‘radio music’ developed within German Neue Sachlichkeit and discusses the relevance of such a concept for current research in the fi eld of radio and music.